Aspectos do sono em pacientes com cirrose hepática - Teodoro, Vinicius Vasconcelos [UNIFESP] (2009)
Hepatic cirrhosis is a serious public health issue in the world, since it was a very common disease, with a great impact. The occurrence of liver structural alterations has various consequences, including neurological ones. The patient with cirrhosis presents several clinical manifestations that involve alterations on his biological functions such as sleep and waking. Study objective: The aim of this study was to characterize sleep parameters and sleepiness in cirrhotic patients and to assess a possible influence the severity level of this disease on these parameters. Design: It was a case-control study. Setting: The hepatology outpatient service of Hospital São Paulo (UNIFESP/EPM) and Sleep Institute and diagnostic center of Associação Fundo de Incentivo à Psicofarmacologia (AFIP). 42 cirrhotic patients and 42 volunteers without hepatic disease were submitted to an all night polysomnographic evaluation. They also answered sleep questionnaires as well as the Epworth Sleepiness Scale. The severity of the illness was assessed by the prognostic model of Child-Turcotte-Pugh and MELD scores. Results: There was no difference in age, gender and BMI between cirrhotic patients and volunteers. However, the polysomnographic findings showed lower sleep efficiency, as well as an increase in the REM sleep latency and a lower REM sleep percentage in the cirrhotic group when compared with the control group. The cirrhotic patients also showed higher frequency of Periodic Limb Movements in Sleep than the controls. There was a significant difference among Child-Turcotte-Pugh groups in regard to REM sleep percentage, significantly lower in group C when compared to group B and group A. No significant differences were detected between the scores of both groups in the Epworth Scale. Conclusion: The findings suggest that cirrhotic patients had a worse quality of sleep when compared with the control group and higher occurrence of PLMS. There was also an influence of the severity of liver failure in some sleep parameters.